A Clinicopathological study of Guillain-Barrḗ Syndrome in a Tertiary Level Hospital - A K M Ferdous Rahman; Mohammad Salim; Saifullah Al Kafi; Saudia Akter Gulshan; Md Imdadul Hoque Chowdhury (Bangladesh Critical Care Journal, 2024)
Background: Guillain-Barre syndrome (GBS) stands out as the most prevalent autoimmune neurological disorder. This investigation involves a comparative analysis of clinical observations, neurophysiological assessments, and cerebrospinal fluid examination, outcomes among patients with GBS. Method: A retrospective review of medical records constituted the methodology for this study, spanning from July 1, 2023, to December 31, 2023. Sociodemographic traits, antecedent illnesses, clinical progression, laboratory results, therapeutic interventions, and ultimate outcomes were assessed and compared among the study participants. Results: The study encompassed 8 patients, with an average age of 42.75 years. Respiratory complications were evident in 87.5% of the patients. In CSF analysis, 62.50% exhibited a normal cell count, while 37.50% displayed an elevated count. Elevated CSF protein levels were observed in 50% of patients, with a corresponding 50% revealing normal CSF protein levels. Increased CSF protein was associated with delayed lumbar puncture, demyelinating nerve conduction study subtype, and sensory motor variant. Regarding treatment modalities, 37.5% received intravenous immunoglobulin, and 25% underwent plasma exchange therapy. The acute phase of the disease resulted in a 25% mortality rate among patients. Conclusion: Guillain-Barre syndrome manifests diverse clinical presentations and laboratory findings. Notably, a high cerebrospinal fluid cell count challenges the widely accepted Brighton criteria for GBS diagnosis. Further investigations are warranted to elucidate the correlation between elevated CSF cell count and other factors influencing pathogenesis and outcomes in GBS patients. Bangladesh Crit Care J March 2024; 12 (1): 25-28